KONTRIBUSI PENGALAMAN PRAKERIN TERHADAP KESIAPAN KERJA SISWA JURUSAN TEKNIK BANGUNAN SMK N 2 PAYAKUMBUH - 695-702 , Deddy Alindra (CIVED, 2015)
Abstract This research started from the high level of rating Unemployment (TPT) graduates Vocational High School (SMK) in Indonesia, especially in West Sumatra. The high level of TPT vocational graduates showed that the failure to achieve the goal of SMK. Students’s Working Readiness to join in the working world are influenced by several factors, one of them is the practical experience outside. At SMK, the practical experience outside are got from the implementation of The Practice of Industrial Work (Prakerin). Based on these symptoms, it can be formulated that the problem in this research is how Prakerin’s  experience contributes  to the students' working readiness. This research is correlation research, which aims to reveal the Prakerin contribution to  the students' working readiness. For that proposed the following hypothesis, experience of The Practice of Industrial Work (Prakerin) contributes students' working readiness in grade XI major in Building Engineering  at SMK N 2 Payakumbuh. The populations in this study are the entire students grade XI major in Building Engineering of SMK N 2 Payakumbuh which has carried out as many as 47 people, using Total Sampling technique.  Based on data analysis, the results are there is weakness relationship between experience of The Practice of Industrial Work with the  Students’s  Working Readiness at  SMK N 2 Payakumbuh especially grade XI major in building engineering.. The relationship is not significant so the experience of Prakerin have low contribute to the students' workimg readiness major in Building Engineering of SMK N 2 Payakumbuh that is equal to 5.66%. Keywords: Contributions,  Practice of Industrial Work, Readiness Work.